Development of muscle power of the lower limbs as a result of training according to the model of modified tactical periodization in young soccer players - Szymanek-Pilarczyk, M.; Nowak, M.; Podstawski, R.; Wasik, J. (Physical Activity Review, 2023)
Muscular power of the lower limbs is an important element in the success of football players. Therefore, the purpose of this work is to evaluate the effect of training according to a modified wave periodization model on the power of lower limbs measured by the length of the long jump of young soccer players. Methods: The study was performed in 2018-2022 in June (test A) and December (test B) of a given year. The measurement was carried out in the form of measuring the length of the long jump from the spot using a measuring tape with an accuracy of ±0.01 m. Results: There was an increase in the length of the long jump between the results of test B compared to the results of test A by an average of 8.32 cm (p<0.01). In general, there is an upward trend in subsequent years. The exception is 2019. It can be noted that the older the athlete, the better the results. No correlation is observed between the position of the athlete and the result of the test conducted. The results from December correlate strongly with the results from June. Conclusions: Based on the conducted research, it can be assumed that the applied training based on the wave periodization model improved the muscular power of the lower limbs of the players of the RKS Raków Czestochowa Academy. This change is important from the point of view of match practice. It was noted that the COVID-19 pandemic affected the deterioration of performance. It can be presumed that the biological development of the subjects influences the increase of the tested physical fitness ability.